Share of women on the executive boards of large companies has increased, but generally Is at most one woman - Virginia Sondergeld; Katharina Wrohlich; Anja Kirsch (DIW Weekly Report, 2024)
The number of women serving on the executive boards of large companies in Germany once again increased in 2023: Around 18 percent (153 of 875) of executive board members at the 200 largest companies were women as of late fall 2023, two percentage points higher than in 2022. Thus, growth has slightly picked up again. In some of the groups of companies analyzed, the figure was even higher. Around 23 percent of executive board members at the DAX 40 companies, for example, are women. The largest banks and insurance companies, which in the past years have lagged considerably behind other private sector companies and companies with government-owned shares, managed to catch up a bit. In many places, this growth is due to the fact that companies have appointed a woman to their executive board for the first time. Beyond that, there is currently not much progress. In addition, the number of women holding the position of CEO has decreased in many groups of companies. More commitment is needed from companies, both internally (e.g., from the supervisory board) and externally (e.g., from investors) to achieve gender parity in senior leadership positions.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; corporate boards; board composition; boards of directors; board diversity; Europe; women directors; executive directors; gender equality; gender quota; Germany; management; private companies; public companies; supervisory boards; executive boards; CEOs; women; finance industry; financial sector; private and public banks; insurance companies